Wybrane aspekty prawnej konstrukcji eWallet - Michał Grabowski (Problemy Zarządzania, 2015)
There are many commercially-functioning electronic (mobile) wallets. Presented examples include MyWallet offered by T-Mobile and Google Wallet. Apart from the payment function, such wallets may have other options, such as collecting loyalty points, buying tickets, storing electronic signatures or certificates. In legal terms, the service consists of a series of legal relations: the software license agreement, the contract for entrusting and processing of personal data as well as the service contract within the meaning of Art. 750 of the Civil Code. Payment functions can be offered directly by the provider of eWallet or provided by third parties. Payment functions (as opposed to other services of eWallet) may, however, be provided only by entities with appropriate administrative permissions (licenses). Therefore, in the legal sense, it is crucial to distinguish which services constitute payment services. In particular, an eWallet itself is not an electronic purse (within the meaning of electronic money instrument) or a payment instrument. The aim of this article is to describe some legal aspects of eWallet, in particular with regard to payment services and services provided by Mobile Network Operators.